Successful Management of Early Postoperative Small Bowel Obstruction Using Steroid: A Case Report - Luthfi, Muhammad; maghfirah, Desi; Yusuf, Fauzi; Abubakar, Azzaki; Syahrin, Alfi; Purnomo, Avisena Gatot (The Indonesian Society for Digestive Endoscopy, 2024)
Background: Early Postoperative Small Bowel Obstruction (EPSBO) is a primary factor contributing to death and morbidity after pelvic and abdominal surgery. Although it is frequently regarded as a surgical emergency, the most recent research indicates that non-operative management is always preferable unless there are complications.Case: A 53-year-old woman came with symptoms of small bowel obstruction and a history of hysterectomy three weeks earlier. The patient refused surgical intervention, so a conservative approach was taken. She was given methylprednisolone 500 mg/day in two doses daily for three consecutive days, in addition to nasogastric tube insertion and symptomatic therapy. After three days of follow-up, the patient showed symptoms improvement, and the abdominal X-Ray and CT Scan showed no abnormal findings.Discussion: The majority of Early Postoperative Small Bowel Obstruction (EPSBO) cases, according to the most recent research, may be managed without surgery. Additionally, due to their anti-inflammatory properties, some medications, like corticosteroids, have been found to be beneficial and effective for EPSBO. This is because they may help resolve the obstruction and lessen the edema and fibrin deposition associated with EPSBO following abdominal surgery.Conclusion: Conservative therapy with steroids appears promising due to its lower risk profile and greater patient comfort. However, the exact mechanism and its efficacy in treating EPSBO have yet to be fully concluded, so further research is still needed.